Effect of different levels of concentrate supplementation on the production performance of Angora rabbits - Bhati, R S; Kumar, Davendra; Sharma, R B; Risam, K S (The Indian Journal of Animal Sciences, 2011)
Experiment was conducted on 54 adult male German Angora rabbits distributed into 3 groups of 18 rabbits in each. Rabbits in T1 were given 140 g pellet feed whereas in T2 and T3 groups were given 110 and 80 g pellet/day. The rabbits in all the groups were given ad lib. fresh wilted roughage. Feed intake and body weight was monitored fortnightly. Rabbits were weighed and sheared after 75 days interval and the experiment was conducted for 375 days up to 4 consecutive shearings. Wool production of 5 consecutive shearings was recorded. Initial body weights of rabbits were 3.13 kg, 3.12 kg and 3.04 kg in T1, T2 and T3 groups, which were 3.28 kg, 3.03 kg and 3.07 kg, respectively, in these groups by the end of fifth shearing. Level of concentrate in the diet did not have any marked effect on body weight. The annual wool yield was 803 g, 772.4 g and 767.4 g in T1, T2 and T3 groups, which was significant among treatments, although there were no differences between T2 and T3 groups. Significant differences were recorded for daily dry matter intake between groups, and also for the digestibility of dry matter, crude fibre and ether extract. Per cent mortality was 11.1 each in T1 and T2 and 27.8 in T3 group. Dry matter required for producing 100 g wool was 7.35 kg in T1, 6.46 kg in T2 and 5.62 kg in T3 group. It is concluded that as almost similar wool production and mortality was observed in groups fed 110 and 140 g concentrate per day along with fulfilling the daily protein requirement, feeding of 110 g of concentrate was found adequate in adult rabbit for economical Angora rabbit production.